Physical Properties and Compressive Strength of Zinc Oxide Nanopowder as a Potential Dental Amalgam Material - Nanang Qosim; Putut Murdanto; Poppy Puspitasari (Institute of Advanced Engineering and Science, 2018)
In this study, the application of nanotechnology was applied in the dentistry field, especially in the innovation of dental amalgam material. To date, mercury (Hg) has been used widely as dental amalgam material with consideration of the cheap price, ease of use, and good mechanical strength. However, last few years, many problems have been faced in the dentistry field due to the use of mercury. Hence, new material is needed as an innovation to eliminate the mercury from dental amalgam composition. This research was conducted to analyze the physical properties and compressive strength of zinc oxide (ZnO) nanopowder as a potential dental amalgam material. The physical properties such as morphology and dimensions were analyzed by SEM and XRD. Further, the compression test was conducted by using hydraulic press machine. The results showed that the ZnO nanopowder analyzed has the particle size of 14.34 nm with the morphology classified as nanorods type. On the compression load of 500 kg, the average of ZnO green density is 3.170 g/cm3. This value experienced the increase of 4.763% when the load was set to 1000 kg, and 7.539% at 2000 kg. The dwelling time also took the same effect. At 30 seconds, the average of ZnO green density is 3.260 g/cm3. This value experienced the increase of 0.583% at 60 seconds and 3.098% at 90 seconds.